2002
DOI: 10.1080/016128402753542983
|View full text |Cite
|
Sign up to set email alerts
|

Behind the Scenes: Spousal Coping Following Permanently Disabling Injury of Farmers

Abstract: Hidden within the pastoral setting of rural America are the struggles of farm families who must cope with a decreasing economy, increasing technology, and one of the highest injury rates of any industry. Wives of farmers often juggle household responsibilities, hold an off-farm job, and work on the farm. Too often, wives are first on the scene of a serious injury to their spouses. All attention is focused on the farmer but the wife must cope with caregiving, her usual work, and the added full responsibility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Depression among farmer caregivers was found in a study of female spouses of acutely injured farmers . Participants noted that assuming new farm responsibilities, caring for the injured spouse, and providing family social support contributed to their depressive symptoms.…”
mentioning
confidence: 99%
“…Depression among farmer caregivers was found in a study of female spouses of acutely injured farmers . Participants noted that assuming new farm responsibilities, caring for the injured spouse, and providing family social support contributed to their depressive symptoms.…”
mentioning
confidence: 99%
“…[17][18][19] The long-term impact of disability may include reduced physical capacity, 17 emotional grief and loss, 16,18 and shifting family roles and responsibilities. 18 Injuries that most commonly result in a disruption of a farmer's career include amputations, spinal cord injuries, and chronic pain.…”
Section: Long-term Effects Of Injury or Illnessmentioning
confidence: 99%
“…They cited attributes such as a sense of humor, perseverance, ability to adapt, personal faith, and the emotional as well as "hands-on" support of spouses, children, and other family members; this finding is in keeping with previous studies. 4,16,19 Farmers, as self-employed managers, reported that they already had many coping skills prior to acquiring the disability. Among them was their ability to make adjustments in the farm operation and to design equipment adaptations that, in the "new or emerging" reality of disability and/or aging, proved to be invaluable.…”
Section: Microsystem Facilitatorsmentioning
confidence: 99%
See 2 more Smart Citations